Beyond Chronic Absenteeism: The Dynamics and Disparities of Class Absences in Secondary School - Jing Liu; Monica Lee (Institute of Labor Economics (IZA), 2022)
Student absenteeism is often conceptualized and quantied in a static, uniform manner, providing an incomplete understanding of this important phenomenon. Applying growth curve models to detailed class-attendance data, we document that secondary school students' unexcused absences grow steadily throughout a school year and over grades, while the growth of excused absences remain essentially unchanged. Importantly, students starting the school year with a high number of unexcused absences, Black and Hispanic students, and low-income students accumulate unexcused absences at a signicantly faster rate than their counterparts. Lastly, students with higher growth rates in unexcused absences consistently report lower perceptions of all aspects of school culture than their peers. Interventions targeting unexcused absences and/or improving school culture can be crucial to mitigating disengagement.
Keywords: I2; 330; student absences; racial disparities; growth curve model; school climate